2007
DOI: 10.1080/14767050601127797
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of endothelin-1 type A receptor gene polymorphism (−231 G > A) in preeclampsia susceptibility

Abstract: No association between the -231 G > A polymorphism in the EDNRA gene and preeclampsia as well as any correlation with the main clinical features of the disorder were found, thus excluding a role for this polymorphism in susceptibility to preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Microarray analysis indicated a number of genes that were up- or down-regulated by the miR-518b mimic. Among the 124 target genes down-regulated more than 2-fold (Supplementary Table S1), two genes (tyrosine hydroxylase: TH and hydroxy-delta-5-steroid dehydrogenase, 3 beta- and steroid delta-isomerase 1: HSD3B1 ) were previously demonstrated to be involved in the pathogenesis of preeclampsia202122, and five genes (endothelin receptor type A: EDNRA , advanced glycosylation end product-specific receptor: AGER , wingless-type MMTV integration site family member 2: WNT2 , complement component 9: C9 , and transient receptor potential cation channel, subfamily M, member 2: TRPM2 ) play roles in preeclampsia with foetal growth restriction23242526272829303132 (Table 1). Likewise, among the 112 target genes up-regulated over 2-fold by the miR-518b mimic (Supplementary Table S2), four genes [hemopexin: HPX , serpin peptidase inhibitor, clade B (ovalbumin), member 2: SERPINB2 , lipoprotein, Lp(a): LPA , and tumour necrosis factor superfamily, member 10: TNFSF10 ] show involvement in preeclampsia35363738, and two genes (CD69 molecule: CD69 and stanniocalcin 1: STC1 ) are involved in preeclampsia with foetal growth restriction333439 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray analysis indicated a number of genes that were up- or down-regulated by the miR-518b mimic. Among the 124 target genes down-regulated more than 2-fold (Supplementary Table S1), two genes (tyrosine hydroxylase: TH and hydroxy-delta-5-steroid dehydrogenase, 3 beta- and steroid delta-isomerase 1: HSD3B1 ) were previously demonstrated to be involved in the pathogenesis of preeclampsia202122, and five genes (endothelin receptor type A: EDNRA , advanced glycosylation end product-specific receptor: AGER , wingless-type MMTV integration site family member 2: WNT2 , complement component 9: C9 , and transient receptor potential cation channel, subfamily M, member 2: TRPM2 ) play roles in preeclampsia with foetal growth restriction23242526272829303132 (Table 1). Likewise, among the 112 target genes up-regulated over 2-fold by the miR-518b mimic (Supplementary Table S2), four genes [hemopexin: HPX , serpin peptidase inhibitor, clade B (ovalbumin), member 2: SERPINB2 , lipoprotein, Lp(a): LPA , and tumour necrosis factor superfamily, member 10: TNFSF10 ] show involvement in preeclampsia35363738, and two genes (CD69 molecule: CD69 and stanniocalcin 1: STC1 ) are involved in preeclampsia with foetal growth restriction333439 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…miR-518b seems to control multiple target genes located on various chromosomes. Interestingly, some miR-518b target genes were previously demonstrated to associate with preeclampsia (e.g., TH and HSD3B1 for down-regulated genes, and HPX, SERPINB2, LPA and TNFSF10 for up-regulated genes)20212235363738 and with preeclampsia with foetal growth restriction (e.g., EDNRA, AGER, WNT2, C9 , and TRPM2 for down-regulated genes, and CD69 and STC1 for up-regulated genes)23242526272829303132333439. However, further experiments are needed to demonstrate a causal relationship between the expression of pregnancy-associated miRNAs and pregnancy-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed a significant association between the TNF-α-308G/A polymorphism and parity (Wang et al, 2018). Similarly, no significant relation in a study by Lisi et al was found between preeclampsia risk factors, such as systolic and diastolic blood pressure, proteinuria and endothelin-1 type-A receptor gene polymorphism (7231 G4A) [40]. Although the current report revealed the genetic association between rs2069740(T/A) and rs34255686(C/A) polymorphisms in the IL-13 gene and the risk of preeclampsia, a more significant sample size is required to validate the observations of the present study.…”
Section: Discussionmentioning
confidence: 87%
“…It is suggested that the fetus itself is also synthesizing the hormone, as a result of hemodynamic and metabolic changes occurring during uterine contractions in childbirth. It is likely that an increased concentration of EDN1in umbilical blood plasma during childbirth leads to the contraction of umbilical vessels after delivery, which may be one of the mechanisms that prepare the fetus for taking the first breath 25 . Plasma endothelin-1 concentrations were similar in preterm and term infants studied by Kuo Cy 26 and Stefanov G et al .…”
Section: Discussionmentioning
confidence: 99%